Propuesta de programa de intervención psicopedagógica en habilidades de interacción social entre estudiantes de educación universitaria - Nizama Reyes, Mario Enrique (2024)
The development of this research aimed to propose the implementation of a psychopedagogical intervention program in basic social interaction skills to enhance interpersonal relationships among university-level students. The research design was not experimental, documentary and propositional; Therefore, there is no population, nor a sample at the level of the intervention groups. The approach addressed was qualitative and descriptive level. In general, we can indicate that the result to be achieved was to establish a frame of reference for the implementation of the intervention program, in addition to selecting the areas of specific skills and sub-skills to cover, which were related to their respective identified ítems from the Social Interaction Skills Questionnaire; to finally outline the proposals for sessions to be executed in the intervention plan. Regarding the conclusions, first of all, it highlights that psychopedagogical intervention must be a highly specialized support process. Secondly, the implementation of the proposed program was only limited to two areas, those related to social interaction and being able to make friends. It was also concluded that the program was structured in seven total sessions and each session lasted one hundred minutes. Finally, highlight that the selected strategies include group dynamics, instruction, practice, feedback, and reinforcement.